Formation of nano-scale FeCO3 protective corrosion product in carbon dioxide-saturated 3 sodium chloride solution - Kakooei, S. (Trans Tech Publications Ltd, 2017)
Corrosion of carbon steel in CO2 saturated NaCl solution contains the formation of FeCO3, as a corrosion product. The protective property of the formed FeCO3 scale layer to corrosion in brine solutions containing CO2 was established as the possible cause of the corrosion rate decrease above 60 °C. In this study, formation of nano-scale FeCO3 film as a corrosion product of X52 carbon steel in CO2-Saturated 3 NaCl solution was investigated. Result showed that corrosion rate decreased after precipitation and formation of protective FeCO3 film in high temperature and high bulk solution pH. © 2017 Trans Tech Publications, Switzerland.